Analysis of Student Information Literacy in State Islamic Religious Universities: Analisis Literasi Informasi Mahasiswa di Perguruan Tinggi Keagamaan Islam Negeri - Solihin, Muhtar Mochamad (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2024)
Background of the study: Students need to have good information literacy in order to complete their studies effectively and efficiently. Purpose: to analyze the characteristics and information literacy of students at State Islamic Religious Universities (PTKIN). Method: quantitative approach with survey methods. Data collection uses online questionnaire distribution. Data analysis techniques use descriptive statistics and inferential statistics. Findings: PTKIN students accessed social media â‰¤ 6 hours every day (60.23%); classified as generation Z (digital natives) aged 10-25 years (98.86%); the number of gadgets owned is 1 (88.64%); the majority have WhatsApp (100%), Instagram (92.05%), YouTube (79.55%) and Twitter (53.41%); the most frequently accessed social media is WhatsApp (61.36%); the purpose of using social media is as a communication tool (83.36%), looking for information to support the thesis (80.68%), looking for entertainment/relaxation (70.45%), sharing information, opinions and/or knowledge (68.18%) , interacting socially (54.55%), interacting with friends (53.41%) and filling free time while waiting for something/free time (53.41%). The information literacy level of students at PTKIN is classified as moderate and tends to be high with an average score between 73 and 90 (73 â‰¤ X < 91). Factors that are positively related to information literacy are the availability of infrastructure, accessibility, independence and social support from lecturers and parents. Only the duration of internet access is negatively related to student information literacy at PTKIN. Conclusion: Students at PTKIN already have sufficient information literacy to support the completion of their studies. However, information literacy needs to be improved in order to maximize study completion on time.